Characterizing the essential oil composition and assessing the antioxidant and antimicrobial properties of two compositae taxa: Gerbera delavayi Franch. and Gerbera piloselloides (L.) Cass - Wu, Junkai; Hu, Wanjun; Chen, Jing; Hu, Jianping; Ke, Cuimin; Sheng, Zunlai (Frontiers in Plant Science, 2025)
IntroductionGerbera piloselloides (L.) Cass. and Gerbera delavayi Franch. are increasingly recognized for their medicinal properties, particularly among ethnic minority communities in southern China, where they are used for heat-clearing, detoxification, cough relief, lung expulsion, and asthma alleviation. Despite their traditional use, these species have been subjected to limited research regarding their biological activities, leaving a gap in scientific understanding. MethodsThis study was designed to investigate the essential oil (EO) compositions, as well as the antioxidant and antimicrobial properties of G. piloselloides and G. delavayi. The EOs were extracted via hydrodistillation and analyzed using gas chromatography-mass spectrometry (GC-MS). The antioxidant potential was assessed through ABTS and DPPH free radical scavenging assays, along with the ferric reducing antioxidant power (FRAP) method. The antimicrobial activity was evaluated against five bacterial strains, including two Gram-positive (Staphylococcus aureus, Listeria) and three Gram-negative (Salmonella, Escherichia coli, Pasteurella multocida) species, using the broth microdilution technique.ResultsThe essential oil from G. piloselloides (EOgp) yielded 0.14% and was found to contain 24 compounds. It demonstrated high antioxidant activity in the ABTS assay and exhibited the strongest antibacterial effect against Listeria in vitro. In contrast, the essential oil from G. delavayi (EOgd) had a higher yield of 0.26% and contained a more complex composition with 100 compounds. It showed superior antioxidant activity in both the DPPH and FRAP assays and also demonstrated the highest antibacterial activity against Listeria.DiscussionThe findings of this study confirm that both G. piloselloides and G. delavayi possess significant potential as natural sources of antioxidants and antibacterial agents, warranting further exploration for their development into therapeutic products.